(untitled) (Research, Society and Development, 2020)
In the context of food quality, Food Fraud has been identified as an emerging risk for the food industry and a significant concern for consumers and official supervisory bodies. Fraud refers to changes in a food product, always for profit, disrespecting the consumer’s right in addition to representing a risk to human health. These frauds have the ability to diminish consumer confidence in their food supply and interfere with the reputation of honest food business operators. Thus, this review aimed to point out the opportunities for fraud and adulteration in some foods, showing the different ways of carrying them out, and also, some cases that have occurred throughout history. While pointing out the need for investment in specific and effective analyzes of production processes by the industries, in addition to control measures, actions aimed at reducing or eliminating possible hazards, which contributed to ensuring the quality and safety of products.